Development and validation of a multivariable prediction model in open abdomen patients for entero‐atmospheric fistula. Issue 5 (4th February 2022) - Cristaudo, Adam T.; Hitos, Kerry; Gunnarsson, Ronny; Decosta, Alan
Abstract: Background: Laparostomy or Open Abdomen (OA) has matured into an effective strategy in the management of abdominal catastrophe. Single prognostic factors have been identified in a previous systematic review regarding entero‐atmospheric fistula (EAF). Unfortunately, no prognostic multivariable model for EAF exist. The aim was to develop and validate a multivariable prediction model from a retrospective cohort study involving three hospital's databases. Methods: Fifty‐seven variables were evaluated to develop a multivariable model. Univariate and multivariable logistic regression analyses were performed for on a developmental data set from two hospitals. Receiver operator characteristics analysis with area under the curve (AUC) and 95% confidence intervals (CI) were performed on the developmental data set (internal validation) as well as on an additional validation data set from another hospital (external validation). Results: Five‐hundred and forty‐eight patients managed with an OA. Two variables remained in the multivariable prediction model for EAF. The AUC for EAF on internal validation were 0.74 (95% CI: 0.58–0.86) and 0.79 (95% CI: 0.67–0.92) on external validation. Conclusions: A multivariable prediction model for EAF was externally validated and an easy‐to‐use probability nomogram was constructed using the two predictor variables. Level of evidence: III; prognostic. Abstract : The list of complications associated with open abdomen management is formidable. Of these, Entero‐Atmospheric Fistula (EAF) is the most feared, associated with mortality, cost and disability. This study produced a simple, yet usable, prediction model for EAF that is internally and externally validated and identifies Aboriginal and/or Torres Strait Islander status and the number of laparotomies as predictive of EAF.